Strategic Flexibility and its Role in Achieving Outstanding Performance: An Analytical Study of the Opinions of Managers of a Number of Telecommunications Companies in The City of Sulaymaniyah - رشيد وريا نجم; محمد شەهلا عبدالله (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The aim of current research was to analyze the nature of the relationship and effect between strategic flexibility and excellence performance, to achieve the objectives of the research, the descriptive analytical approach applied to survey the views of managers in a number of telecommunications companies in the city of Sulaymaniyah, which numbered (14) companies. The questionnaire was Distributed to all sample of the study directly as well as electronically via (Google Form). A set of statistical methods were used to analyze the data by using the statistical package (SPSS V.26) & (AMOS V.26), and the research reached a set of results, the most important of which is the existence of a direct correlation between strategic flexibility and excellence performance, in addition strategic flexibility have a significant effect in general on excellence performance, and based on the conclusions, a set of proposals has been formulated, the most important of which is that the researched companies are keen to increase interest in the flexibility of the strategy and its dimensions because of its significant impact on achieving excellence performance, and consequently enhancing its capabilities to enable it to sustain superiority over competitors as well as to lead the market and its reflection on its capabilities in enabling it to successfully exploit the opportunities available in the external environment.